National Multicenter Study on the Prevalence of Carbapenemase-Producing Enterobacteriaceae in the Post-COVID-19 Era in Argentina: The RECAPT-AR Study - Echegorry, Mariano (2024)
The COVID-19 pandemic has exacerbated the global antimicrobial resistance (AMR) crisis.Consequently, it is more urgent than ever to prioritize AMR containment and support countriesin improving the detection, characterization, and rapid response to emerging AMR threats. Weconducted a prospective, multicenter study to assess the prevalence of carbapenemase-producingEnterobacterales in infectious processes in Argentina during the post-COVID-19 pandemic periodand explore therapeutic alternatives for their treatment (RECAPT-AR study). Methods: A total of182 hospitals participated by submitting Enterobacterales clinical isolates to the National ReferenceLaboratory (NRL) during the first three weeks of November 2021. Inclusion criteria were defined asan ertapenem MIC ≥ 0.5 mg/L, a zone diameter ≤ 22 mm. Carbapenemase genes and those codingfor major extended-spectrum β-lactamases were molecularly characterized using multiplex PCRat the NRL. Antibiotic susceptibility testing followed international standards (CLSI and EUCAST).Results: The NRL analyzed 821 Enterobacterales isolates. Metallo-β-lactamase (MBL, 42.0%) and KPC(39.8%) accounted for 81.8% of carbapenemases, followed by OXA-163 (7.4%), a variant of OXA-48with additional activity against extended-spectrum cephalosporins, and enzyme combinations (8.3%).These combinations included NDM plus KPC (3.4%), OXA-163 plus KPC (2.4%), and OXA-163 plusNDM (2.1%). Klebsiella pneumoniae was the main species recovered, representing 76% of the isolates.According to the carbapenemase classes or combinations, tigecycline exhibited a susceptibility rangeof 33–83%, fosfomycin 59–81%, colistin 27–78%, and amikacin 17–81%. Ceftazidime-avibactam (CZA)and imipenem-relebactam (IMR) showed 92% and 98% susceptibility against serine carbapenemases,respectively. Meanwhile, aztreonam-avibactam (AZA) exhibited 96–98% susceptibility against allcarbapenemase classes. Conclusions: A new epidemiological landscape has emerged, characterizedby the equivalent circulation of NDM and KPC. K. pneumoniae remains the primary species responsiblefor their dissemination. The co-production of carbapenemase combinations, particularly KPC plusNDM, was confirmed, mainly in K. pneumoniae. High activity was observed for AZA against MBLsand for CZA and IMR against KPC and OXA-163 carbapenemases.